Integrated water resource systems: theory and policy implications - Keller, A.; Keller, J.; Seckler, D. (International Irrigation Management Institute, 1996)
Presents the concept of integrated water resources systems (IWS) as clearly and simply as possible, with a focus on the irrigation sector-the largest and most complex user of water.